The Effect Of Providing Dash (Dietary Approaches To Stop Hypertension) Diet Education On Diet Compliance In Hypertension Patients - Zavira, Aulia Diva; Ariyani, Anita Dwi; Balqis, Rani Diana (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2025)
Currently, hypertension is one of the most common diseases suffered by peoples. Hypertension is characterized by an increase in blood pressure above normal limits. The large number of hypertension sufferers is caused by unhealthy eating patterns, therefore, to prevent hypertension, it is necessary to carry out a hypertension diet by providing DASH diet education. The study aims to determine the effect of DASH diet education on diet compliance in hypertension sufferers. This study is a quantitative study with a quasi-experimental design of two groups pre and post test with group control. The sampling technique used purposive sampling with a total of 48 samples divided into intervention groups and control groups. The variables in this study were the provision of DASH diet education and diet compliance. The instruments used were the DASH diet education SAP, animated videos and Diet Compliance Questionnaires. The DASH instrument is a valid and reliable measuring tool. Then analyzed using the Mann Withney. The results of the Mann Withney analysis in the intervention group showed an Asymp. Sig. value of 0.000 (<0.05) which means that there is an effect of DASH diet education on hypertension diet compliance. In the control group, there was no change in the pre-post test data, so the Asymp. Sig. value did not appear in the analysis results, thus it can be concluded that there is no effect of providing DASH diet education on dietary compliance of hypertension sufferers. Based on the research results, DASH diet education can increase compliance with hypertension diet in respondents. It is expected that respondents can understand the substance of DASH diet education and continue to implement it in everyday life in order to undergo a hypertension diet program so that blood pressure remains under control.